Palm kernel shell as partially replacement of fine aggregates in concrete - Ahmed Ashraf, Zaki Mohd (2015)
This final year project discussed mainly about the feasibility of using the palm kernel shell as a partial replacement of fine aggregates in concrete. This studied were used the different percentage of palm kernel shell as a partial replacement of fine aggregates in concrete at 1%, 2%, and 3% by volume of sand. Palm kernel shells are derived from the oil palm tree (elaeis guineensis), an economically valuable tree because of its oil. Palm kernel shells have been used as aggregates in light and dense concretes for structural and non-structural purposes. Palm kernel shell were obtained from the Lepar Hilir palm oil mill and sieved with size between l.5mm to 2.36mm. The objectives of this final year project are to determine the workability, compressive strength and also flexural strength of concrete when adding with 1%, 2% and 3% of palm kernel shell as a replacement of fine aggregates in concrete. All of the testing were followed the British standard. The workability of concrete were tested by using slump test to check the consistency of freshly made concrete. For compressive strength total of 27 cubes with size 150mm x 150mm x 150mm were used to determine the compressive strength of concrete when replace with 1%, 2% and 3% of palm kernel shell as a replacement of fine aggregates in concrete. Then for flexural strength total of 27 beams with size 100mm x 100mm × 500mm were used to determine the flexural strength of concrete when replace with 1%, 2% and 3% of palm kernel shell as a replacement of fine aggregates in concrete. Compressive and flexural strength were conducted at 7 days, 14 days, and 28 days to get the strength of concrete. All of the testing were compared with normal concrete. As the result were obtained, it can concluded that replacement of palm kernel shell with 1% replacement had a probability to use as a sand replacement in construction industry